2017
DOI: 10.1002/acm2.12188
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric validation of Monaco treatment planning system on an Elekta VersaHD linear accelerator

Abstract: The purpose of this study is to perform dosimetric validation of Monaco treatment planning system version 5.1. The Elekta VersaHD linear accelerator with high dose rate flattening filter‐free photon modes and electron energies was used in this study. The dosimetric output of the new Agility head combined with the FFF photon modes warranted this investigation into the dosimetric accuracy prior to clinical usage. A model of the VersaHD linac was created in Monaco TPS by Elekta using commissioned beam data includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Absolute percent point dose differences were <2% for all studied cases. Another study on VersaHD model validation in Monaco found an average gamma pass rate of (93.8% ± 4.7%) based on 2%global/2mm criteria for eight types of IMRT test field plans, and an average gamma pass rate of 95% based on 3%global/3 mm criteria for eight re‐planned patient cases . Absolute percent point dose differences measured in a homogeneous phantom were <2% for all cases in the same study.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Absolute percent point dose differences were <2% for all studied cases. Another study on VersaHD model validation in Monaco found an average gamma pass rate of (93.8% ± 4.7%) based on 2%global/2mm criteria for eight types of IMRT test field plans, and an average gamma pass rate of 95% based on 3%global/3 mm criteria for eight re‐planned patient cases . Absolute percent point dose differences measured in a homogeneous phantom were <2% for all cases in the same study.…”
Section: Discussionmentioning
confidence: 78%
“…A commercial DICOM‐RT‐based plan and delivery verification system Mobius (Mobius Medical Systems, Houston, TX, acquired by Varian recently) was commissioned to provide routine IMRT QA and to independently validate Eclipse model in addition to the ionization chamber and film measurements. The feasibility and accuracy of using Mobius for second dose check was reported in previous studies . The commissioning was a similar iterative process involving Mobius DLG adjustments through plan recalculation for Mobius and Eclipse dose comparisons.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…Existem diversos sistemas comercias para planejamento para teleterapia, tais como: iPlan RT (BrainLAB A.G., Heimstetten, Germany) 23 , XiO (Elekta AB, Stockholm, Sweden) 24,25 , Monaco (Elekta AB, Stockholm, Sweden) [26][27][28] , Pinnacle (Philips Radiation Oncology Systems, Fitchburg, WI) 29,30 , Eclipse (Varian Medical Systems, Palo Alto, CA, USA) 31,32 , RayStation 33,34 e Panther 3D 35,36 .…”
Section: Sistemas De Planejamento Em Teleterapia Com Fótonsmentioning
confidence: 99%